2008
DOI: 10.1007/s00128-008-9366-0
|View full text |Cite
|
Sign up to set email alerts
|

Tree Rings, Populus nigra L., as Mercury Data Logger in Aquatic Environments: Case Study of an Historically Contaminated Environment

Abstract: In this study, a tree (Populus nigra L.) has been presented as data logger of mercury release in aquatic environments using tree rings chemistry to provide chronological historical monitoring of mercury discharge from a chlor-alkali industrial effluent to a coastal lagoon. Tree rings (Populus nigra L.) as mercury data logger is suggested by mercury accumulation trends in the tree rings reflecting the industrial plant capacity increments in the early stages of mercury discharges and enhancing industrial plant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Sheppard et al (2008) provided a similar confirmation of a dendrochemical signal for sulfur (S) and phosphorus (P), associated with the 1943 volcanic eruption of Paricutin, Mexico. Abreu et al (2008) confirmed the synchronous dendrochemical uptake of anthropogenic mercury released by a chlor-alkali plant in Portugal.…”
Section: Have Dendrochronology and Forensic Dendrochemistry Been Thorsupporting
confidence: 76%
“…Sheppard et al (2008) provided a similar confirmation of a dendrochemical signal for sulfur (S) and phosphorus (P), associated with the 1943 volcanic eruption of Paricutin, Mexico. Abreu et al (2008) confirmed the synchronous dendrochemical uptake of anthropogenic mercury released by a chlor-alkali plant in Portugal.…”
Section: Have Dendrochronology and Forensic Dendrochemistry Been Thorsupporting
confidence: 76%
“…Overall, Hg concentrations at the TC sites were low due a lack of point sources for air pollution and no mining activity proximate to the catchment area. Other studies, adjacent to point source pollution and contaminated with legacy Hg, have measured concentrations up to 280 and 644 ng g –1 in wood , (Table SI 1). Also, the TC trees did not exhibit an increase in Hg concentrations consistent with the timing of the Industrial Revolution.…”
Section: Resultsmentioning
confidence: 99%
“…Climate change could be the most important reason for the intensification of this process [ 56 ]. At different geographic scales, the interaction of these factors establishes chronological profiles with different temporal variations of contamination specific to each ecosystem [ 5 , 57 , 58 ]. Therefore, it is crucial to analyze climate change’s effects on the intensification of some mechanisms triggering higher Hg bioaccumulation in the aquatic ecosystems of this region.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation trends have been inferred mostly from records in sediment layers, but in recent years, dendrochemistry has provided great insights into environmental and social histories. Biologists, climatologists and physical geographers have used dendrochronological techniques to investigate environmental changes and recent global climate changes in different parts of the world [ 37 , 38 , 58 , 59 , 60 , 61 , 62 , 63 ]. Dendrochronological methods have successfully dated and interpreted geological and hydrological conditions [ 64 ], avalanches and rock falls [ 65 ], archaeological sites’ human activity [ 4 ] and climate change [ 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation